(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The concept of socio-spiritual environment is defined differently by different scientists and specialists. For example, in “Spirituality. Dictionary of Basic Concepts”, without specifically considering the socio-spiritual environment, the concept of “social environment” is defined as “a set of material and spiritual conditions that form the basic knowledge, experience and skills, characteristics of a person as a social being. This research work also presents ideas, considerations, and analyses on ensuring the stability of the socio-spiritual environment.